Problem Issues and Prospects of Implementation of Technologies Declaration of Customs Transit Procedure in Electronic Form as a Tool to Improve the Quality of Customs Services - A. S. Abramov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
One of the performance indicators of customs authorities is the speed of customs operations, which is considered as the defining indicator of the quality of customs services. The leadership of the Federal Customs Service pays much attention to this issue, which is expressed in the establishment of relevant indicators of the effectiveness of the activities of customs authorities, both at the crossing of the customs border of the Eurasian Economic Union, and when placing goods under the declared customs procedure. One of the promising tools for improving the quality of customs services is the declaration of the procedure for customs transit in electronic form. In connection with the relative novelty of this technology, as well as the lack of requirements for the mandatory submission of an electronic transit declaration, the management of the Federal Customs Service established an index of the efficiency of activities, expressed in the filing of electronic transit declarations in the amount of 10, 15 and 20% of the total array of transit declarations in 2, 3 and 4 quarters of 2017. The introduction of electronic transit technology at the current stage is connected with the presence of a number of problematic issues related to the actual imposition of additional encumbrances on participants in foreign economic activity in the form of the need to obtain an electronic digital signature, the formation of a formalized type of shipping documents, or the conclusion of contracts with a customs representative for the performance of the above operations. However, in the short term, the aforementioned costs can be offset by a reduction in the burden on a number of carriers associated with providing compliance with the customs transit procedure, as well as a significant reduction in the time costs associated with customs operations if the electronic form of the transit declaration is included in the customs control mechanism of goods on the principles of a through process of customs control.